Improving health literacy through adult basic education in Australia. (25th May 2017) - Morony, Suzanne; Lamph, Emma; Muscat, Danielle; Nutbeam, Don; Dhillon, Haryana M; Shepherd, Heather; Smith, Sian; Khan, Aisha; Osborne, Julie; Meshreky, Wedyan; Luxford, Karen; Hayen, Andrew; et al.
Summary: Adults with low literacy are less empowered to take care of their health, have poorer health outcomes and higher healthcare costs. We facilitated partnerships between adult literacy teachers and community health providers to deliver a health literacy training program in adult basic education classrooms. Following course completion we interviewed 19 adult education teachers (15 delivering the health literacy program; 4 delivering standard literacy classes) and four community health providers (CHPs) about their experiences, and analysed transcripts using Framework analysis. Written feedback from eight teachers on specific course content was added to the Framework. Health literacy teachers reported a noticeable improvement in their student's health behaviours, confidence, vocabulary to communicate about health, understanding of the health system and language, literacy and numeracy skills. CHP participation was perceived by teachers and CHPs as very successful, with teachers and CHPs reporting they complemented each other's skills. The logistics of coordinating CHPs within the constraints of the adult education setting was a significant obstacle to CHP participation. This study adds to existing evidence that health is an engaging topic for adult learners, and health literacy can be successfully implemented in an adult basic learning curriculum to empower learners to better manage their health. Health workers can deliver targeted health messages in this environment, and introduce local health services. Investment in adult literacy programs teaching health content has potential both to meet the goals of adult language and literacy programs and deliver health benefit in vulnerable populations.